Detection of Bacterial Endospores in Soil by Terbium Fluorescence. (7th July 2011) - Brandes Ammann, Andrea; Kölle, Linda; Brandl, Helmut
Abstract : Spore formation is a survival mechanism of microorganisms when facing unfavorable environmental conditions resulting in "dormant" states. We investigated the occurrence of bacterial endospores in soils from various locations including grasslands (pasture, meadow), allotment gardens, and forests, as well as fluvial sediments. Bacterial spores are characterized by their high content of dipicolinic acid (DPA). In the presence of terbium, DPA forms a complex showing a distinctive photoluminescence spectrum. DPA was released from soil by microwaving or autoclaving. The addition of aluminium chloride reduced signal quenching by interfering compounds such as phosphate. The highest spore content (up to 10 9 spores per gram of dry soil) was found in grassland soils. Spore content is related to soil type, to soil depth, and to soil carbon-to-nitrogen ratio. Our study might provide a basis for the detection of "hot spots" of bacterial spores in soil.